Production of Quinone Enzyme from Nicotiana tabacum Cell Culture Using Immobilized Dry Plant Foam - Teuku Maimun; Mirna Rahmah Lubis; Komala Pontas; Anwar Thaib; Abubakar Abubakar (Journal of Applied Technology, 2023)
A study of immobilization of Nicotiana tabacum cell culture to increase the concentration of the quinone enzyme CoQ10 has been carried out. The immobilization medium was in the form of dry plant foam (dry ridge gourd). Cell growth and concentration of quinone enzyme were measured by fresh weight of the cell and High-Performance Liquid Chromatography methods, respectively. Immobilization of the Nicotiana tabacum plant cell culture was effective for cell growth, and increase CoQ10 concentration. CoQ10 concentration from the immobilized cell culture of the Nicotiana tabacum plant was 0.060 mg/g fresh cell weight after seven days of cultivation. The optimum temperature for the concentration of CoQ10 enzyme was 35°C.